ChemInform Abstract: Mechanisms of Fibrinogen Adsorption at Solid Substrates. Issue 52 (10th December 2015) - Adamczyk, Zbigniew; Bratek‐Skicki, Anna; Zeliszewska, Paulina; Wasilewska, Monika
Abstract: Review: 100 refs.